Historiography of Christianity in India - Webster, John C. B., 1935- (New Delhi : Oxford University Press, 2012)
Consists of 7 previously published articles mostly lightly reworked for inclusion in this volume.
The history of Christianity in India: aims and methods -- The historian and theological research in India -- The identity of Indian Christians -- A quest for the historical Ditt -- The women of Amritsar through missionary eyes -- Christian history as Indian social history: a review of the literature -- Dalit Christian history: themes and trends -- Conclusion: examining basic assumptions.
Includes bibliographical references (p. [251]-265) and index.
Keywords: Christianity -- India -- Historiography; Christianity -- India -- History